2006
DOI: 10.1097/01.ta.0000195996.73186.2e
|View full text |Cite
|
Sign up to set email alerts
|

Negative Pressure Wound Therapy to Treat Hematomas and Surgical Incisions Following High-Energy Trauma

Abstract: NPWT has been used on many complex traumatic wounds. Potential mechanisms of action include angiogenesis, increased blood flow, and decreased interstitial fluid. This ongoing randomized study has demonstrated decreased drainage and improved wound healing following both hematomas and severe fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
240
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(252 citation statements)
references
References 34 publications
(30 reference statements)
5
240
0
7
Order By: Relevance
“…The incidence of SSI in 2012 was 0.10% (1/964). Application of NPWT to a closed incision has been shown to reduce incidence of infection and dehiscence [7,8]. Although none of the year by year changes is significant, the overall change in incidence of SSI from 2.13% to 0.1% is a statistically significant reduction (p < 0.0001).…”
Section: Resultsmentioning
confidence: 82%
“…The incidence of SSI in 2012 was 0.10% (1/964). Application of NPWT to a closed incision has been shown to reduce incidence of infection and dehiscence [7,8]. Although none of the year by year changes is significant, the overall change in incidence of SSI from 2.13% to 0.1% is a statistically significant reduction (p < 0.0001).…”
Section: Resultsmentioning
confidence: 82%
“…[31][32][33] The usefulness was also shown in the management of fasciotomies in of our patients which received NPWT followed by closure either by secondary intent or by skin grafting. 34 DeFranzo and colleagues reported a case series that observed NPWT applied to decreased edema of open fractures and decreased circumference of the extremity and size of the wound; 95% of wounds were successfully closed. 34 Other studies have also used NPWT for managing the fasciotomy wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, another recent study suggested that NPWT was associated with a reduction in the size of post-operative seromas after total hip arthroplasty 37 . Moreover, Stannard et al 38 undertook a RCT investigating NPWT versus pressure dressing or standard post operative dressing in high-risk lower extremity fractures and concluded that NPWT reduced the duration of drainage in patients with haematomas or high-risk lower limb fractures compared with controls (mean 1.6 days versus 3.1 days for haematomas, p=0.03; and 1.8 days versus 4.8 days for high-risk fractures, p=0.02) 38 .…”
Section: Discussionmentioning
confidence: 99%